2020
DOI: 10.1093/plcell/koaa017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a photosynthetic cyanobacterium rich in internal membrane systems via gradient profiling by sequencing (Grad-seq)

Abstract: Although regulatory small RNAs have been reported in photosynthetic cyanobacteria, the lack of clear RNA chaperones involved in their regulation poses a conundrum. Here, we analyzed the full complement of cellular RNAs and proteins using gradient profiling by sequencing (Grad-seq) in Synechocystis 6803. Complexes with overlapping subunits such as the CpcG1-type versus the CpcL-type phycobilisomes or the PsaK1 versus PsaK2 photosystem I pre(complexes) could be distinguished, supporting the high quality of this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 120 publications
5
40
0
Order By: Relevance
“…Gradient profiling by sequencing and mass spectrometry (Grad-Seq) is a hybrid complexome analysis that combines density gradient centrifugation with quantitative protein mass spectrometry with RNA-seq and has the power to quantitatively profile transcripts or non-coding RNA that co-segregate with proteins. [20,58,[67][68][69].…”
Section: Rna-protein Complexesmentioning
confidence: 99%
“…Gradient profiling by sequencing and mass spectrometry (Grad-Seq) is a hybrid complexome analysis that combines density gradient centrifugation with quantitative protein mass spectrometry with RNA-seq and has the power to quantitatively profile transcripts or non-coding RNA that co-segregate with proteins. [20,58,[67][68][69].…”
Section: Rna-protein Complexesmentioning
confidence: 99%
“…To date, Grad-seq has been used to profile stable RNPs in several model bacteria, such as the γ-proteobacteria S. Typhimurium (Smirnov et al, 2016;Gerovac et al, 2020;Venturini et al, 2020), Escherichia coli (Hör et al, 2020a), and Pseudomonas aeruginosa (Gerovac et al, 2021), the firmicute Streptococcus pneumoniae (Hör et al, 2020b), the cyanobacterium Synechocystis sp. (Riediger et al, 2020), and even in human cells (Aznaourova et al, 2020). Additionally, the RNPs formed by P. aeruginosa RNAs have been analyzed along with phage KZ transcripts during viral infection in what can be considered the first "dual Gradseq" experiment (Gerovac et al, 2021).…”
Section: Case Study: Comparative Analysis Of Bacterial Stable Rnpsmentioning
confidence: 99%
“…Given that yggL is mostly expressed in the exponential phase, and its deletion has a strong effect on the 50S levels, the protein likely functions in late LSU assembly (Chen and Williamson, 2013;Smirnov et al, 2016;Hör et al, 2020a). This specific example provides a modus operandi to study other candidate ribosome biogenesis factors spotted by Grad-seq, especially in less studied species (Hör et al, 2020b;Riediger et al, 2020).…”
Section: Class Iib: New Ribosome Assembly Factorsmentioning
confidence: 99%
“…In contrast, the CRISPR3 system (sll7085-sll7090) on the same plasmid was consistently down-regulated at RNA and protein level. Recently, it has been shown that these proteins form a stable protein complex together with their cognate crRNAs (Riediger et al, 2021).…”
Section: Salt Stress Differentially Affects Chromosome Regionsmentioning
confidence: 99%